RESEARCHING TYPES OF PARALINGVISTIC TOOLS IN MODERN LINGUISTICS - Ganiyeva Moxidil Mo'ydinjon qizi; Kuldashev Nizomiddin (Scholars Digest Publishing, 2023)
In this article nonverbal communication is researched in various cultures and countries. Methods for using body language to increase coomunicative approaches with non-verbal tools effectively are proposed, as wel as ways , to have a fruitable or profitable communication in speech among people in bussness and daily life. In conclusion the great attention is drawn to results on using non-verbals in different cultures.
Keywords: communication tools, verbals, non-verbals, culture, body language, eye contact, posture, gesture, facial expression.